Distinct properties of hexameric but functionally conserved Mycobacterium tuberculosis transcription-repair coupling factor. - Swayam Prabha; Desirazu N Rao; Valakunja Nagaraja (PLoS ONE, 2011)
Transcription coupled nucleotide excision repair (TC-NER) is involved in correcting UV-induced damage and other road-blocks encountered in the transcribed strand. Mutation frequency decline (Mfd) is a transcription repair coupling factor, involved in repair of template strand during transcription. Mfd from M. tuberculosis (MtbMfd) is 1234 amino-acids long harboring characteristic modules for different activities. Mtbmfd complemented Escherichia coli mfd (Ecomfd) deficient strain, enhanced survival of UV irradiated cells and increased the road-block repression in vivo. The protein exhibited ATPase activity, which was stimulated ∼1.5-fold in the presence of DNA. While the C-terminal domain (CTD) comprising amino acids 630 to 1234 showed ∼2-fold elevated ATPase activity than MtbMfd, the N-terminal domain (NTD) containing the first 433 amino acid residues was able to bind ATP but deficient in hydrolysis. Overexpression of NTD of MtbMfd led to growth defect and hypersensitivity to UV light. Deletion of 184 amino acids from the C-terminal end of MtbMfd (MfdΔC) increased the ATPase activity by ∼10-fold and correspondingly exhibited efficient translocation along DNA as compared to the MtbMfd and CTD. Surprisingly, MtbMfd was found to be distributed in monomer and hexamer forms both in vivo and in vitro and the monomer showed increased susceptibility to proteases compared to the hexamer. MfdΔC, on the other hand, was predominantly monomeric in solution implicating the extreme C-terminal region in oligomerization of the protein. Thus, although the MtbMfd resembles EcoMfd in many of its reaction characteristics, some of its hitherto unknown distinct properties hint at its species specific role in mycobacteria during transcription-coupled repair.